Insight into Prolonged Cycling Life of 4 V All‐Solid‐State Polymer Batteries by a High‐Voltage Stable Binder. Issue 1 (17th November 2020) - Liang, Jianneng; Chen, Dachang; Adair, Keegan; Sun, Qian; Holmes, Nathaniel Graham; Zhao, Yang; Sun, Yipeng; Luo, Jing; Li, Ruying; Zhang, Li; Zhao, Shangqian; Lu, Shigang; et al.
Abstract: Polyethylene oxide (PEO) based solid polymer electrolytes (SPEs) are incompatible with the 4 V class cathodes such as LiCoO2 due to the limited electrochemical oxidation window of PEO. Herein, a number of binders including commonly used binders PEO, polyvinylidene fluoride (PVDF), and carboxyl‐rich polymer (CRP) binders such as sodium alginate (Na‐alginate) and sodium carboxymethyl cellulose, are studied for application in the 4 V class all‐solid‐state polymer batteries (ASSPBs). The results show ASSPBs with CRP binders exhibit superior cycling performance up to 1000 cycles (60% capacity retention, almost 10 times higher than those with PEO and PVDF binders). Synchrotron‐based X‐ray absorption spectroscopy (XAS), morphology studies and density functional theory studies indicate that, with their carboxyl groups, CRPs can strongly bind the electrode materials together, and work as coating materials to protect the cathode/SPE interface. Cyclic voltammetry studies indicate that CRP binders are more stable at high voltage compared to PEO and PVDF. The stability under high voltage and the coating property of CRP binders contribute to stable cathode/SPE interfaces as disclosed by the X‐ray photoelectron spectroscopy and Co L‐edge XAS results, enabling long cycling life, high performance 4 V class ASSPBs. Abstract : The most used binder in high voltage solid polymer batteries is polyethylene oxide (PEO), which has a high ionic conductivity but a low electrochemical oxidation window. This study shows carboxyl‐rich polymers have superior high voltage stability compared to PEO, and can work as coating materials to protect the cathode/polymer electrolyte interface, thus, enabling a long cycling life high voltage solid polymer battery.